Synthesis of SnO2 by chemical routes and its use in varistors production - Mosquera, A.; Rodriguez-Paez, J. E.; Varela, José Arana [UNESP]; Bueno, Paulo Roberto [UNESP] (Elsevier B.V., 2007)
Tin oxide, SnO2. is a very used compound in industry and one of its uses is as varistor. For the current requirements of the technology is necessary a strict control of the chemical purity and the particle size of the raw material; for that reason the great interest that exists at the moment to develop synthesis methods that allow to get these requirements. In this work, ceramic powders of the Sn-Co-Nb-Ti-Al system using the controlled precipitation and polymeric precursor (Pechini) methods were synthesized. The raw material obtained was characterized using X-ray diffraction (XRD), thermal analysis (DTA/FG) and scanning electron microscopy (SEM). The sintering samples shown a good varistor behavior with non-linear coefficient (alpha) values similar to 22, and Er 2083 V/cm(2). (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: synthesis; powders-chemical preparation; electrical properties; varistors